Productivity Measurement with Natural Capital and Bad Outputs - Brandt, Nicola (OECD Publishing, 2014)
This paper presents a productivity growth measure that explicitly accounts for natural capital as an input factor and for undesirable goods, or "bads", as an output of the production process. The discussion focuses on the extension of productivity measurement for bad outputs and estimates of their shadow prices, while the inclusion of natural capital is discussed in more depth in a companion paper. As bad outputs are the target of environmental policies, a productivity measure that does not take bad outputs into account will underestimate productivity growth, whenever countries devote some inputs to reducing bad outputs, thus improving the environmental impact of their production processes, rather than to increasing the production of goods and services. An adjusted productivity measures is needed in an analysis of the effect of bad outputs on productivity growth as otherwise the effectiveness of environmental policies in promoting production processes that make more efficient use of the environment will be wrongly assessed. Results suggest that the adjustment of the traditional productivity growth measure for bad outputs is small. While this partly hinges on the fact, that due to a lack of more comprehensive data, only a limited set of bad outputs are considered in this paper, namely CO2, SOX and NOX emissions, the relatively small adjustment of the traditional productivity growth measure is good news for two reasons. First, it implies that ignoring the bad outputs considered in this paper results in a relatively small bias of productivity measurement, and thus analysis based on traditional measures should be relatively reliable in this regard. Second, it also implies that the acceleration in productivity growth that would help to substantially reduce the bad outputs considered in this paper, without reducing output growth, should be possible to achieve
Keywords: Energy; Environment; Economics